Analisis Bahan Ajar Literasi dan Numerasi di Sekolah Dasar - Ayuningrum Ayuningrum; Mabruroh Mabruroh; Ratna Sari Dewi (Departement of Mathematics Education, 2023)
This examination means to depict the idea of learning the executives in working on the nature of training in the This paper highlights the importance of literacy and numeracy competencies, along with the Pancasila values, in the Graduation Competency Standards for basic education. These efforts are part of the implementation of human resource strengthening in line with national policies and the strategies of the Ministry of Education and Culture (Kemendikbud). Literacy and numeracy are fundamental skills for students, with literacy encompassing reading and writing skills, and numeracy involving mathematical abilities and the application of numerical concepts in daily life. In addition to character education, literacy and numeracy have become top priorities for the Ministry of Education and Culture. In the context of the Merdeka Belajar (Independent Learning) policy, the roles of teachers, parents, schools, and the environment significantly influence the success of student learning. This paper discusses strategies for enhancing students' literacy and numeracy skills and the implementation of numeracy literacy within the curriculum and daily learning activities.